Entrepreneurial Orientation in Mexican Microenterprises - Héctor Montiel Campos; Luis S. Alvarado Acuna; José Pablo Nuno de la Parra; Francisco A. Aguilar Valenzuela (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Over the past 30 years research on Entrepreneurship Orientation (EO) has provided valuable information regarding strategy, entrepreneurship and aspects of performance at the firm-level. In the entrepreneurial universe, microenterprises play a very special role in the business context of the economy. However, they have not been relatively present in the EO research. This paper studies the EO-performance relationship in a group of microenterprises in Mexico and includes the Dominant Logic (DL) as a variable that moderates this relationship. The results indicate that risk taking, proactiveness and competitive aggressiveness variables from the EO influence the microenterprise performance. In addition, the external DL conceptualization moderates the EO-performance relationship. This paper shows the conclusions of the investigation as well as the limitations and identifies future research methods.